Big and tall parents do not have more sons - Kevin Denny (University College Dublin, UCD School of Economics, 2007)
In a 2005 paper Kanezawa proposed a generalisation of the classic Trivers-Willard hypothesis. It was argued that as a result taller and heavier parents should have more sons relative to daughters. Using two British cohort studies, evidence was presented which was partly consistent with the hypothesis. I analyse the relationship between an individual being male and their parents' height and weight using one of the datasets. No evidence of any such relationship is found.
Keywords: 330; Biologie; Eltern; Kinder; Geschlecht